Revisiting the therapeutic potential of gingerols against different pharmacological activities - Sharma, Samridhi; Shukla, Monu Kumar; Sharma, Krishan Chander; Tirath; Kumar, Lokender; Anal, Jasha Momo H.; Upadhyay, Santosh Kumar; Bhattacharyya, Sanjib; Kumar, Deepak (Naunyn-Schmiedeberg's archives of pharmacology, 2023)
The rhizomes of ginger have been in use in many forms of traditional and alternative medicines. Besides being employed as condiment and flavoring agent, it is used in the treatment of nausea, osteoarthritis, muscle pain, menstrual pain, chronic indigestion, Alzheimer’s disease, and cancer. Ginger rhizome contains volatile oils, phenolic compounds and resins, and characterization studies showed that [6]-gingerol, [6]-shogaol, and [6]-paradol are reported to be the pharmacologically active components. Gingerol is a major chemical constituent found as volatile oil in the rhizomes of ginger. It has several medicinal benefits and used for the treatment of rheumatoid arthritis, nausea, cancer, and diabetes. Many studies have been carried out in various parts of the world to isolate and standardize gingerol for their use as a complementary medicine. The present review summarizes wide range of research studies on gingerol and its pharmacological roles in various metabolic diseases. Graphical Abstract